American Carrier Air Power at the Dawn of a New Century - Lambeth, Benjamin S. (RAND Corporation, 2005)
In the Afghanistan war, U.S. carrier-based fighters substituted almost entirely for land-based theater air forces. The Navy's carriers again played a key role in conducting around-the-clock operations against Saddam Hussein's forces in Iraq. American carrier air power is now able to conduct coordinated deep-strike missions well beyond coastal reaches. The Navy's performance over Afghanistan and Iraq showed how the nation's carrier force can provide around-the-clock target coverage, consistently accurate target attack, and multiple successful target attacks per sortie.